Adverse events of group psychotherapy in the in‐patient setting – results of a naturalistic trial. (31st May 2017) - Schneibel, R.; Wilbertz, G.; Scholz, C.; Becker, M.; Brakemeier, E.‐L.; Bschor, T.; Zobel, I.; Schmoll, D.
Abstract : Objective: Adverse events of psychotherapy have often been neglected in research. In this study, potential adverse events of group psychotherapies in a psychiatric hospital were systematically assessed, explored for predictors and linked to treatment outcome. Method: A naturalistic trial was conducted in 180 in‐patients attending different group psychotherapies. Adverse events were assessed using three different measures: (i) weekly reporting of unwanted treatment reactions, (ii) mood changes in response to every single group session and (iii) premature group termination. Results: Different measures of adverse events were weakly associated. Deterioration of mood state and/or unwanted treatment reactions were experienced by 60–65% of all patients. Reports of unwanted treatment reactions decreased over time and were negatively associated with symptom improvement. However, mood state deterioration was constant and unrelated to treatment outcome. The rate of premature group termination was 34%. Significant predictors of adverse events included patient characteristics as well as disadvantageous group conditions. Conclusions: For the majority of patients, group psychotherapy in the in‐patient setting is associated with adverse events. Changes over time and a strong correlation with general symptom severity must be considered in the assessment and interpretation of adverse events. Predictors should be considered as potential risk factors in future research.